Tyrosine Kinase Inhibitor Tyrphostin AG490 Inhibits Osteoclast Differentiation in Collagenase-Induced Osteoarthritis. (May 2014) - Gyurkovska, V.; Dimitrova, P.; Ivanovska, N.
The janus kinase (JAK)-signal transducer and activator of transcription (STAT) cascade plays a principal role in the signaling of a vast array of cytokines and growth factors which stimulates diverse cellular functions and immune responses. Osteoarthritis (OA) is the most common joint disease in the adult population. The present study was designed to evaluate the effects of tyrosine kinase inhibitor, tyrphostin AG490 in a mouse model of collagenase-induced osteoarthritis (CIOA). CIOA was provoked by two intraarticular (i.a.) injections of collagenase in mice and intraperitoneally (i.p.) treated with AG490 at a dose of 5 mg/kg at days 0, 5 and 10 and at a dose of 8 mg/kg at day 18. The administration of AG490 in CIOA mice inhibited osteoclast generation in bone and the loss of glycosaminoglycans and proteoglycans in cartilage. Tyrphostin decreased the levels of IFN-γ, IL1, IL-6 and IL-17 in the synovial fluid (SF) dependant on the time post AG490 administration. Limited numbers of CD11b positive Ly6G neutrophils in blood and SF along with a decrease of F4/80 positive cells in synovial fluid (SF) were observed in tyrphostin AG490-treated arthritic mice. AG490 inhibited M-CSF+RANKL-induced cytokine production by bone marrow (BM) cells and the differentiation of BM cells in vitro . Because of the findings presented, we argue that tyrphostin AG490 may hold promising therapeutic potential against important clinical conditions such as osteoarthritis (OA).